The Impact Of Oral Health Literacy On Dental Anxiety And Utilization Of Oral Health Services Among Dental Patients - Alrashidi, Amnah Nashi Bnai; Alrimi, Haneen Tariq Mohammed; Alzahrani, Mohammed Abduallah Ahmed; Alzahrani, Sultan Abdulrhman Mohammed; Alzahrani, Mohammed Ahmed Saeed; Alsayegh, Homood Mohammed; Alwadai, Naif Mohsen S; Maroof, Faisal Ali; Alsobhi, Samir Waslullah O; Almutairi, Sana Abdullah; Almutiri, Abeer Abdullah (Migration Letters, 2023)
Background: Low oral health literacy levels and deficient oral health knowledge risk the communication between dentists and patients in different communities. This study aimed to examine the impact and association of oral health literacy with patients’ levels of dental anxiety and their utilization of dental health services. Methods: A cross-sectional study was conducted at King Khalid University Dental Clinics, KSA. The study utilized a structured, interview led questionnaire that was administered by dental patients. A total of 440 patients interviewed a convenience sample of 440 dental patients: including 269 females (61.1%) and 171 males (38.9%). The questionnaire consisted of four sections; a demographic section, a modified Arabic Rapid Estimate of Adult Literacy (ARELAD-30) Tool that measures the ability of the participants to read 30 commonly used dental terms. This questionnaire was modified by the researchers to measure the participants’ knowledge by asking them to choose the most accurate meaning for each word based on their previous knowledge. Scoring was dependent on the participant’s immediate correct pronunciation, as well as comprehension of each word. The Arabic Modified Dental Anxiety Scale (AMDA[1]S) was used to measure the level of dental anxiety, and the dental health service utilization was measured using the Utilization of oral health services questionnaire. Results: One quarter (24.1%) of the participants read the 30 items of the A-REALD correctly. The average percentage of correct responses to the meaning of the dental terms was 71.2%. There was no statistically significant association between A-REALD and knowledge scores (Spearman’s Correlation coefficient ρ = -0.008, p-value = 0.872). There was a statistically significant inverse correlation between age and MDAS (Correlation coefficient ρ = -0.146, p-value = 0.002). A-REALD scores were inversely correlated with time since last visit (Regression coefficient = -0.027, p-value = 0.036, with 95% CI: -0.052 – -0.002). Conclusion: It can be concluded that oral health literacy is significantly associated to dental health services utilization, while, dental anxiety is related to other variables, such as age and gender.